KESADARAN HUKUM WAJIB PAJAK DALAM PEMBAYARAN PAJAK BUMI DAN BANGUNAN (Studi Penelitian di Badan Pengelolaan Keuangan Daerah Kota Lhokseumawe) - Hidayatullah, Putra; Arnita, Arnita; Muhibuddin, Muhibuddin (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2025)
This study discusses the legal awareness of taxpayers in paying Land and Building Tax (PBB) at BPKD Lhokseumawe City. The UN is important for regional revenue and the development of regional autonomy, but taxpayer awareness still faces obstacles. The objectives of this study include: (1) Identifying taxpayers' legal awareness, (2) Uncovering BPKD's obstacles in increasing taxpayer awareness, and (3) Knowing BPKD's efforts in increasing legal awareness of PBB payments. The research method uses an empirical legal approach with direct interviews. This research is descriptive and analytical, referring to Law Number 12 of 1994 and Qanun Aceh Number 1 of 2024. The results of the study show that taxpayers' awareness is influenced by knowledge of regulations, the application of sanctions, and communication between taxpayers and BPKD The obstacles found include lack of education, limited resources, and ineffective communication. BPKD's efforts include counseling, socialization, and the application of administrative sanctions. The conclusion shows that collaboration between BPKD and taxpayers, effective communication, and intensive education can increase legal awareness of UN payments. With this approach, regional revenues can be managed effectively, and tax awareness can grow for the welfare of the community and regional development.